O Fazer semiótico do Conto Popular Nordestino: intersubjetividade e inconsciente coletivo - Arrais, Maria Nazareth de Lima (2011)
Popular narratives are rich in elements of the natural world in which underlie unconscious contents. This survey brought a reflection over the images of the collective unconscious in the relations of intersubjectivity found in folktales from the Brazilian Northeast. This concern came from the fact that the human being is not only seen as a biological structure, but also as social and psychic structure. Under this view, we sought for more satisfactory positions on the significance of folktales. We started from the assumption that underlying the discourse of the folktale, there are images of the collective unconscious, capable of describing the relations of intersubjectivity, meaning that intersubjectivity as a form of constitution of subjectivity emerges under the subject's performance in relation to otherness and the archetypes of the collective unconscious manifested symbolically through myths, magic and fantasy. The research was conducted from the general objective that was proposed to examine, under the interface between Semiotics and Psychoanalysis that is present in images of the collective unconscious intersubjective relations of enunciation and utterance that characterize the northeastern folktale, in order to perceive aspects identify the subjects, the relations among them and between subjects and between subject and object of their value. The theoretical basis focused Greimasian semiotics explaining the semiotic function, from a generative trajectory composed of three levels: narrativization, speechlization and deep semantics. The analysis was complemented by this tensive semiotics of Fontanille which accounts for inflections of axiological values from an intense and extensive grading. It was discussed too, the theories of the unconscious, from Freud and Jung who, in addition to a personal unconscious, proposes a collective. Then we tried to see how "self" is constructed, following the understanding that subjectivity is constituted as otherness. To situate the corpus, we discussed about the literature of the folktale, especially considering the origin, structure and identification according to Nascimento s Catalogue of Brazilian Folktale. This research consisted of two hundred and eighty thousand of which were selected among those nine versions from the Northeast Brazil. The stories were coded by the initial graphemes of words in the title: As mil e uma noites (MN), O macaco e o rabo (MR), A Moura Torta (MT); Seu Nino (SN) As perguntas de Dom Lobo (PDL); Boi Leição (BL) and A Aranha Caranguejeira e o Quibungo (ACQ), O macaco e a cabaça (MC), A menina dos brincos de ouro (MBO). Before the analysis, it was built a synopsis and segmentation. In narrative structure, one identified the semiotic subject, searching for their value objects, sometimes aided by an adjuvant, sometimes hampered by an opponent. In the discourse structure, we analyzed their interpersonal relations of space and time, enunciation and statement, in which the symbolic richness of the stories revealed the presence of the major archetypes of the collective unconscious: the animus, the anima, the shadow, the persona and Self, who spoke on different images and contributed to the perception of the various issues. In the fundamental structure, it was elucidated the opposition of good versus evil as the matrix pole for the emergence of other oppositions.